Aid on demand: African leaders and the geography of China's foreign assistance - Dreher, Axel; Fuchs, Andreas; Hodler, Roland; Parks, Bradley; Raschky, Paul A.; Tierney, Michael J. (AidData working paper series, 2016)
This article investigates whether China's foreign aid is particularly prone to capture by political leaders of aid-receiving countries. We examine whether more Chinese aid is allocated to the birth regions of political leaders and regions populated by the ethnic groups to which leaders belong, controlling for indicators of need and various fixed effects. We have collected data on 117 African leaders' birthplaces and ethnic groups and have geocoded 1,650 Chinese development finance projects across 3,097 physical locations that were committed to Africa over the 2000-2012 period. Our econometric results show that when leaders hold power their birth regions receive substantially more funding from China than other subnational regions. We also find — less robust — evidence that African leaders direct more Chinese aid to areas populated by individuals who share their ethnicity. However, when we replicate the analysis for the World Bank, our regressions show no evidence of favoritism. We also evaluate the impact of Chinese aid on regional development, exploiting time variation in the amount of Chinese aid that results from China's production of steel and geographical variation in the probability that a subnational region will receive such aid. We find that Chinese aid improves local development outcomes, as measured by per-capita nighttime light emissions at the first and second subnational administrative level. We therefore conclude that China's foreign aid program has both distributional and developmental consequences for Africa